THE CRITICAL PERIOD HYPOTHESIS IN LANGUAGE LEARNING (Modern education and development, 2025)
According to the Critical Period Hypothesis (CPH), language acquisition is most successful within a physiologically defined window of time.  It is thought that this phase ends  around adolescence, at which point learning a language becomes much more challenging and time-consuming.  Since its initial formulation by Eric Lenneberg in 1967, the hypothesis has served as a fundamental component of research on language acquisition and psycholinguistics.  There is conflicting but generally positive evidence from a large number of research concerning first and second language acquisition.  For example, younger second-language learners generally attain higher skill levels than adults, while children who are denied language input early in life frequently fail to properly acquire language later. Recent research using neuroimaging has also suggested age-related differences in brain plasticity associated with language learning. This article explores both classical and contemporary research on the topic, discusses counterarguments, and evaluates implications for language education. The findings indicate that while age is a significant factor, other variables—such as motivation, exposure, and context—also play a crucial role in language acquisition success.